1998
DOI: 10.1007/s004670050503
|View full text |Cite
|
Sign up to set email alerts
|

Expression of type IV collagen in the developing human kidney

Abstract: The distribution of alpha1-6 chains of type IV collagen (alpha1-6(IV)) in human fetal kidneys was examined by indirect immunofluorescence. By 11 weeks of gestation, alpha1, 2, 3, 4, and 6(IV) were already present, but alpha5(IV) appeared relatively late, at 21 weeks. Alpha1(IV) and alpha2(IV) were present in all basement membranes, alpha3(IV) and alpha4(IV) were restricted to the glomerular basement membrane and parts of the tubular basement membrane. Alpha5(IV) was distributed in the glomerular basement membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Since in glomeruli, the production of the collagen IV α3α4α5 heterotrimer is restricted to podocytes [12], their involvement in AS pathogenesis is of great interest. Recently, the analysis of kidney biopsies of AS patients clearly showed that podocyte loss starts as early as birth and results in the progressive reduction of podocyte number per glomerulus with time, correlating with overall renal damage [13].…”
Section: Introductionmentioning
confidence: 99%
“…Since in glomeruli, the production of the collagen IV α3α4α5 heterotrimer is restricted to podocytes [12], their involvement in AS pathogenesis is of great interest. Recently, the analysis of kidney biopsies of AS patients clearly showed that podocyte loss starts as early as birth and results in the progressive reduction of podocyte number per glomerulus with time, correlating with overall renal damage [13].…”
Section: Introductionmentioning
confidence: 99%
“…As already described, the major cell receptors for type IV collagen are α 1 β 1 and α 2 β 1 integrins [116]which recognize and bind to specific fragments of the collagen molecule. Expression patterns have been established for all six α isoforms in fetal and adult kidney [117, 118, 119, 120]. In fetal tissues, α 1 and α 2 are found fairly ubiquitously throughout all BMs.…”
Section: Ligands For Integrin Binding – the Bm Networkmentioning
confidence: 99%
“…Furthermore, synchronous expression of these α chains in the otic vesicle and pronephros support an evolutionary conserved anatomic specificity for α3α4α5 synthesis, given that this protomer is the major component of the cochlear and glomerular basement membranes in humans. The chains expression enabling α3α4α5 network synthesis is not detectable in these organs until late time points, which supports a similar, evolutionary conserved, collagen IV isoform switching event in these tissues [62, 63].…”
Section: Discussionmentioning
confidence: 71%
“…For example, during human nephrogenesis, the GBM is initially comprised of the collagen IV α1α2α1 protomer. As the glomerulus matures, the GBM collagen IV undergoes an isoform switch from the α1α2α1 to the α3α4α5 protomer [62, 63]. Our results show that the expression of the more specialized α3α4α5 protomer was not detected by in situ hybridization in many of the zebrafish organs during embryonic development.…”
Section: Resultsmentioning
confidence: 86%